Description of the larva and redescription of the adult male of Diamphipnoa helgae Illies, 1960 (Plecoptera: Diamphipnoidae) - Pessacq, Pablo (2012)
Based on specimens reared in situ in the National Park "Los Alerces", Chubut Province, Argentinean Patagonia, we describe the larvae and redescribe the adult male of Diamphipnoa helgae Illies, 1960.